KESEMPURNAAN CINTA KASIH DALAM PERNIKAHAN TANPA ANAK - Alfredsius Ngese Doja; Yosafat Reynaldi K. Alfanov; Yohanes Endi (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2024)
The focus of this study is to explore the meaning of love for married couples who have not been blessed with children. The methodology used is a qualitative study with a phenomenological approach. Data processing techniques were carried out using the Interpretative Phenomenological Analysis (IPA) method with several sources of online articles. The lives of married couples are unique in their daily lives when they are not blessed with children. When everyone lives as a married couple, they really hope for the presence of children. In this undesirable situation, the couple was able to rise. This is what will be studied in this research, namely why married couples are able to rise from resilience. The purpose of this study is to find out what kind of love is lived by married couples who have not been blessed with children. Researchers found that in looking at a marriage the presence of children is not the only goal of marriage. Then good communication between married couples can strengthen the relationship between them.